Quantification of Energetic Electron Precipitation Driven by Plume Whistler Mode Waves, Plasmaspheric Hiss, and Exohiss. Issue 7 (8th April 2019) - Li, W.; Shen, X.‐C.; Ma, Q.; Capannolo, L.; Shi, R.; Redmon, R. J.; Rodriguez, J. V.; Reeves, G. D.; Kletzing, C. A.; Kurth, W. S.; Hospodarsky, G. B.
Abstract: Whistler mode waves are important for precipitating energetic electrons into Earth's upper atmosphere, while the quantitative effect of each type of whistler mode wave on electron precipitation is not well understood. In this letter, we evaluate energetic electron precipitation driven by three types of whistler mode waves: plume whistler mode waves, plasmaspheric hiss, and exohiss observed outside the plasmapause. By quantitatively analyzing three conjunction events between Van Allen Probes and POES/MetOp satellites, together with quasi‐linear calculation, we found that plume whistler mode waves are most effective in pitch angle scattering loss, particularly for the electrons from tens to hundreds of keV. Our new finding provides the first direct evidence of effective pitch angle scattering driven by plume whistler mode waves and is critical for understanding energetic electron loss process in the inner magnetosphere. We suggest the effect of plume whistler mode waves be accurately incorporated into future radiation belt modeling. Plain Language Summary: Electron precipitation into Earth's upper atmosphere is an important loss mechanism of energetic electrons trapped in the inner magnetosphere. Although whistler mode waves are known to be effective in producing electron precipitation through pitch angle scattering, the relative roles of various whistler mode waves that play in electron losses are unclear. In this letter, we quantitatively analyze conjunction events, where Van Allen Probes observed various whistler mode waves near the equator and Low‐Earth‐Orbiting satellites detected electron precipitation approximately along the same magnetic field line but at low altitudes. By combining the satellite data analysis and quasi‐linear theory, we found that whistler mode waves observed in plumes are very effective in scattering energetic electrons, which are ultimately lost through interacting with the neutral atmosphere. Our new finding provides the direct evidence that plume whistler mode waves play an important role in energetic electron precipitation, which is crucial for understanding energetic electron loss process in the Earth's inner magnetosphere. Key Points: Three types of whistler mode waves are observed during conjunction events between Van Allen Probes and POES/MetOp These whistler mode waves include plume whistler mode waves, plasmaspheric hiss, and exohiss Plume whistler mode waves are very effective in producing energetic electron precipitation (from tens to hundreds of keV)